2008
DOI: 10.1177/1362361308097118
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition in faces and the use of visual context Vo in young people with high-functioning autism spectrum disorders

Abstract: We compared young people with high-functioning autism spectrum disorders (ASDs) with age, sex and IQ matched controls on emotion recognition of faces and pictorial context. Each participant completed two tests of emotion recognition. The first used Ekman series faces. The second used facial expressions in visual context. A control task involved identifying occupations using visual context. The ability to recognize emotions in faces (with or without context) and the ability to identify occupations from context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 43 publications
8
47
3
2
Order By: Relevance
“…In participants with ASD decreased recognition accuracy for emotions is reported not only for basic emotions (Ashwin et al 2006;Wright et al 2008) but also for complex emotions such as smugness, awkwardness and concern (Golan et al 2006): adults with autism performed poorly when they were asked to identify complex emotions and mental states from social interactions in short video scenes (Golan et al 2006). Performance was also impaired when emotions had to be identified in a social context providing only motion cues but no facial expressions, as in computerized animations of geometric figures (Boraston et al 2007).…”
Section: Emotion Processingmentioning
confidence: 96%
See 1 more Smart Citation
“…In participants with ASD decreased recognition accuracy for emotions is reported not only for basic emotions (Ashwin et al 2006;Wright et al 2008) but also for complex emotions such as smugness, awkwardness and concern (Golan et al 2006): adults with autism performed poorly when they were asked to identify complex emotions and mental states from social interactions in short video scenes (Golan et al 2006). Performance was also impaired when emotions had to be identified in a social context providing only motion cues but no facial expressions, as in computerized animations of geometric figures (Boraston et al 2007).…”
Section: Emotion Processingmentioning
confidence: 96%
“…Discrepancies were most apparent for fear, disgust, and happiness. In a study with children with autism Wright et al (2008) identified anger and happiness as the most challenging emotions to be recognized from a face.…”
Section: Emotion Processingmentioning
confidence: 99%
“…In keeping with this suggestion, high-functioning individuals with autism (HFA), who do not have intellectual impairment (i.e., IQs > 70), appear relatively unimpaired in their ability to recognise expressions of non-social emotions in the faces of photographed actors (e.g., Heerey, Keltner, & Capps, 2003;Rutherford & Towns, 2008;van der Geest, Kemner, Verbaten, & Engeland, 2002;Wright et al, 2008; for alternative explanations and findings see e.g., Grossman, Klin, Carter, & Volkmar, 2000;Hobson, 1991;Wallace, Coleman, & Bailey, 2008). Amongst lowfunctioning individuals with autism (LFA), who do have accompanying learning disability (i.e., have IQs of 70 or below), there is greater evidence of deficits in the recognition of non-social emotions (e.g., Braverman et al, 1989;Hobson, 1982Hobson, , 1986.…”
Section: Introductionmentioning
confidence: 99%
“…[50] Ancak bazı çalışmalarda önceki çalışmaların aksine yaş ve zekâ düzeylerine göre eşleştirilmiş otistik çocukların yüz ifadelerini tanımakta farklılık göstermediği bildirilmiştir. [29,51] Buna rağmen otistik çocuklarda görüldüğü gibi erişkin OSB'li bireylerin de negatif yüz duygularını tanıma zorluklarının sürdüğü bildirilmiştir. [52] Yetişkin OSB'lilerde hem yüz tanıma hem de duyguların yüz ifadelerini tanıma kusurları sürmek-tedir.…”
Section: çOcuklarda Duygu Tanıma Gelişimiunclassified